Hubungan Antara Budaya Organisasi dan Komunikasi Interpersonal dengan Kinerja Karyawan Staff di Perusahaan Pelayaran PT. Buana Listya Tama - Bobi Satria; Aprizawati Aprizawati; Adiat Adiat (Journal of Management and Bussines (JOMB), 2023)
The purpose of this research is to find out the factors that influence work discipline and self-leadership on the performance of employees at PT. Buana Listya Tama Tbk (Company), in encouraging the growing interest of all employees and leaders to carry it out in their respective fields of work, so that everyone in the company feels involved with the company's organizational culture. The research method used is a survey applying the type of correlational research. The results of the proposed research prove that the variables of leadership style (X1), work discipline (X2), both individually and collectively have a positive and significant relationship with employee performance (Y). In conclusion, the three independent variables of leadership style (X1) and work discipline (X2) are variables that need attention. In other words, that the three independent variables of leadership style (X1) and work discipline (X2) are quite effective variables for improving employee performance. Keywords: Organizational Culture, Interpersonal, Communication, Performance